2021
DOI: 10.1111/cod.13804
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and severity of hand eczema in the general population – A systematic review and meta‐analysis

Abstract: Accurate assessments of the burden of hand eczema (HE) in the general population are important for public awareness and intervention. The aim of this systematic review and meta-analysis was to provide updated estimates of prevalence and incidence, alongside additional epidemiological endpoints on HE in the general population.PubMed, Embase and Web of Science were searched for studies reporting the prevalence and/or incidence of HE in the general population. Proportion meta-analyses were performed to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
115
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 82 publications
(133 reference statements)
10
115
3
3
Order By: Relevance
“…Compared to other studies, our estimates were remarkably lower: Quaade et al performed a systematic review 5 on studies published between 1964 and 2019 and calculated a pooled lifetime HE prevalence of 14.5%. This review contained 66 studies on HE, of which 22 (including 151 693 persons) were considered for lifetime prevalence estimation.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Compared to other studies, our estimates were remarkably lower: Quaade et al performed a systematic review 5 on studies published between 1964 and 2019 and calculated a pooled lifetime HE prevalence of 14.5%. This review contained 66 studies on HE, of which 22 (including 151 693 persons) were considered for lifetime prevalence estimation.…”
Section: Discussioncontrasting
confidence: 80%
“…We did not use estimates from these studies to conduct sensitivity analyses with our data because Meding et al 29 as well as Svensson et al 30 considered self‐reports for current hand eczema and not self‐reported physician‐diagnosed lifetime hand eczema as in our study. In general, sensitivity of self‐reported HE is considered to be low 5,31 . In addition, self‐reports on physician‐diagnosed HE tend to underestimate the true prevalence, as mentioned by Quaade et al 5 Therefore, it would be speculative to apply the sensitivity and specificity from one of those validity studies mentioned above to our estimates.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations